2022
DOI: 10.1002/app.52622
|View full text |Cite
|
Sign up to set email alerts
|

A disposable ultrasensitive surface enhanced Raman spectroscopy biosensor platform fabricated from biodegradable zein nanofibers

Abstract: In this paper, a natural polymer, zein, is converted into a disposable and environmentally friendly surface enhanced Raman spectroscopy (SERS) biosensor platform to detect toxins. First, protein nanofiber mats were fabricated using electrospinning. Next, the surface of the fibers was decorated with metallic nanoparticles to create hotspots for the detection of the target molecule. Four types of metallic nanoparticles were tested for sensitivity optimization: gold, silver, silver‐shelled‐gold, and a mixture of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 56 publications
1
3
0
Order By: Relevance
“…Some acrylamide peaks are overlapping with some of the zein peaks. The peaks obtained for zein nanofibers for this study were in accordance with other reported studies [ [18] , [22] , [23] ].
Fig.
…”
Section: Resultssupporting
confidence: 92%
See 2 more Smart Citations
“…Some acrylamide peaks are overlapping with some of the zein peaks. The peaks obtained for zein nanofibers for this study were in accordance with other reported studies [ [18] , [22] , [23] ].
Fig.
…”
Section: Resultssupporting
confidence: 92%
“…4 (c)) resulting from improved dispersion, increased surface area, conductivity, and stronger interaction between the nanoparticles and the composite fiber blends although the exact mechanism of growth and corresponding kinetics of the formation of such structures is not clear [ [15] , [20] , [21] ]. Article [ 22 ] studied four types of metallic nanoparticles (gold, silver, silver-shelled-gold, and a mixture of gold and silver nanoparticles) embedded into zein/acrylamide nanofibers. An increase in concentration of the nanoparticles was observed to have sufficient influence in the distribution uniformity of the nanofibers therefore this observation correlated to the morphological observations of the current study.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on the characteristics of electrospun matrix embedded components, biosensors with distinct functions are achievable. Highly enhanced sensitivity for the presence of carcinogenic acrylamide was obtained by fabricating zein mats decorated with the precise arrangement of gold and silver nanoparticles [ 39 ]. More recently, a biosensor based on electrodes coated with curcumin carbon dots and zein electrospun nanofibers, detected S. aureus in milk using electrical impedance spectroscopy [ 40 ].…”
Section: Recent Trends In Biomedical Application Of Electrospun Plant...mentioning
confidence: 99%
“…Figure 11 shows different types of polymer nanofiber Raman sensors for the detection of pH, the mixture of Sudan I, CV and MG molecules, and H 2 O 2, OCHO. (1) For biological applications, Zhao et al [15], Zhu et al [100], Turasa et al [101], and Wang et al [102] used nanofibers to detect various biological molecules, such as neurotransmitters, metabolites, toxins, and bacteria. They exploited the high surface area and biocompatibility of nanofibers to enhance the sensitivity and selectivity of their sensors.…”
Section: Raman Sensormentioning
confidence: 99%